2017
DOI: 10.1155/2017/4129459
|View full text |Cite
|
Sign up to set email alerts
|

Moringa oleifera Seeds Attenuate Vascular Oxidative and Nitrosative Stresses in Spontaneously Hypertensive Rats

Abstract: Moringa oleifera (MOI) is a tree currently used in traditional medicine in tropical Africa, America, and Asia for therapeutic applications in several disorders including arterial hypertension. We previously described a cardiac protective role of a treatment with MOI seeds in spontaneously hypertensive rats (SHR). Here, we investigated the effects of this treatment on oxidative and nitrosative vascular stresses in SHR, with normotensive Wistar Kyoto rats used as controls. Oxidative and nitrosative stresses dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 39 publications
2
25
0
Order By: Relevance
“…The isolated four pure compounds, niazinin A, niazinin B, niazimicin and niazinin A + B—from ethanol extract of MO leaves showed a blood pressure lowering effect in rats, mediated possibly through a calcium antagonist effect [ 14 , 95 ]. A recent study reported that MO reduced vascular oxidation in spontaneously hypertensive rats [ 96 ].…”
Section: Effects Of Moringa Oleifera On the Prementioning
confidence: 99%
“…The isolated four pure compounds, niazinin A, niazinin B, niazimicin and niazinin A + B—from ethanol extract of MO leaves showed a blood pressure lowering effect in rats, mediated possibly through a calcium antagonist effect [ 14 , 95 ]. A recent study reported that MO reduced vascular oxidation in spontaneously hypertensive rats [ 96 ].…”
Section: Effects Of Moringa Oleifera On the Prementioning
confidence: 99%
“…Moringa has also remarkable antioxidant, anti-inflammatory and immunomodulatory activities. The antioxidant activity is particularly strong in leaves 61 , but also pods 62 and seeds 63 showed similar effects. Studies with normal and diabetic rats documented significant increase in the activity of the enzymes superoxide dismutase, catalase and glutathione S-transferase and decreased lipid peroxidation in response to treatment with aqueous leaf extracts.…”
Section: Effects Of Moringa Oleifera On the Prevention Of Chronic Dismentioning
confidence: 83%
“…Thiocarbamate and isothiocyanate glycosides (Faizi et al, ), methyl phydroxybenzoate and β‐sitosterol (Faizi et al, ) isolated from pods are known for hypotensive activity. Seeds demonstrated vascular oxidative and nitrosative stresses in spontaneously hypertensive rats (Randriamboavonjy, Rio, Pacaud, Loirand, & Tesse, ). Niazinin‐A, niazinin‐B, and niazimicin found in ethanolic extract of leaves are effective in controlling the blood pressure level possibly through a calcium antagonist effect (Anwar et al, ; Dubey, Dora, Kumar, & Gulsan, ).…”
Section: Resultsmentioning
confidence: 99%